2023
DOI: 10.3233/jnd-221638
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI Abnormalities, Epilepsy and Intellectual Disability in LAMA2 Related Dystrophy – a Genotype/Phenotype Correlation

Abstract: Background: LAMA2-related muscular dystrophy is a disorder that causes muscle weakness and varies in severity, from a severe, congenital type to a milder, late-onset form. However, the disease does not only affect the muscles, but has systemic involvement and can lead to alterations such as brain malformation, epilepsy and intellectual disability. Objective: Describe the frequency of cortical malformations, epilepsy and intellectual disability in LAMA2-RD in a Brazilian cohort and correlate the neurological fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Therefore, the suspicion of LAMA2-RDs in patients of this origin should prompt a search for this specific mutation. The c.5234+1G>A mutation was identified in five patients from Portugal and seven from Brazil [25][26][27]. The c.5562+5G>C variant was predominantly observed in patients from the UK [6,28,29].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, the suspicion of LAMA2-RDs in patients of this origin should prompt a search for this specific mutation. The c.5234+1G>A mutation was identified in five patients from Portugal and seven from Brazil [25][26][27]. The c.5562+5G>C variant was predominantly observed in patients from the UK [6,28,29].…”
Section: Discussionmentioning
confidence: 95%
“…Besides, 10 patients were identified as LGMD-like phenotype cases. Among individuals with severe MDC1A (n=68), 16 patients had a homozygous genotype, 50 patients exhibited a compound heterozygous genotype characterized by a splice-site mutation combined with another loss-of-function mutation (splicing/frameshift/nonsense), and only two patients had a splice-site mutation associated with a missense mutation [6,7,11,17,18,[24][25][26][30][31][32][33][34][35][36][37][38][39][40][41]. Of the 68 severe MDC1A cases, 32 patients had documented results regarding the level of laminin-α2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LAMA2 gene is the most common cause of MDC1A, 53 Nevertheless, the condition has a widespread impact and affects not just the muscles but can also cause brain malformations, mental retardation, and other alterations. 54 Moreover, it is frequently accompanied by seizures. Electroencephalogram (EEG) showed that temporal and occipital epilepsy was the most common, further proving that the right transverse temporal might be the primary brain region affected by the LAMA2 gene.…”
Section: Discussionmentioning
confidence: 99%